Performance analysis of ship-to-ship communication using automatic identification system (AIS) - Su, Zhengyang (2019)
The Automatic Identification System (AIS) is a new type of marine navigation aid that can receive information from the very high frequency (VHF) band in real time. It is used for ship-to-ship/shore communication, effectively avoiding significant maritime accidents. Commercial available VHF/UHF can be used for short range communication and satellite services for longer range ones. This report focuses on the performance of ship-to-ship communication using AIS. The communication channel model using Matlab is developed and presented. The signal at transmitter is designed according to AIS frame structure. And the receiver is developed to test bit error rate through different non-coherent demodulation ways. The performance in this report of communication system is simulated by Monte Carlo method. Firstly, this report introduces AIS and its specific parameters in practical . Then the principle of GMSK modulation and demodulation is presented along with Matlab code list. Then communication channel model is developed and different parameters are set to test the performance. Finally, at the receiving end, we compute bit error rate of AWGN, Rician and Rayleigh channel and compare them. At the end of report, the recommendations for the future work to further improve the project is mentioned.